The effect of sharing a mother tongue with peers: Evidence from North Carolina middle schools - Thomas Ahn; Christopher Jepsen (IZA Journal of Migration, 2015)
This paper provides the first analysis of the relationship between the language mix of Limited English Proficient (LEP) peers and student achievement, using detailed panel data from 2006 to 2012. Percent LEP has a negative association with mathematics and reading test scores, more so for non-LEP students than for LEP students. The overall language mix of LEP students has little if any discernable relationship with achievement. For LEP students, having more LEP peers speak their mother tongue is positively associated with reading achievement and negatively associated with mathematics achievement.
Keywords: I21; I28; J15; 330; Limited English Proficiency; Peer effects; Student achievement